Is pneumoperitoneum specific of post-traumatic appendicitis? Case report and literature review - Y. Kerkeni; F. Thamri; A. Zouaoui; S. Houidi; R. Jouini (SpringerOpen, 2022)
Abstract Introduction Acute appendicitis and blunt abdominal trauma may co-exist, imposing a dilemma of whether there is only coincidence or there is a cause to effect relationship. The etiopathogenesis of this rare association remains obscure. Pneumoperitoneum has rarely been described in patients with acute perforative appendicitis following abdominal trauma. Case presentation We report a rare case of acute perforated appendicitis after blunt abdominal trauma in an 8-year-old boy revealed by a pneumoperitoneum. We also reviewed the literature on this rare condition to assess the specificity of pneumoperitoneum in the diagnosis and to understand its etiopathogenesis. Conclusion Abdominal pain and fever several days after an abdominal trauma may be a sign of post-traumatic appendicitis in the pediatric population. Pneumoperitoneum is not specific of post-traumatic appendicitis but it can be a protective sign, since it will lead to immediate laparotomy in patients with an unrecognized surgical abdomen.